Integration Tlocor Marine Tourism Destinations In Realizing Smart Village To Improve The Local Community’s Economy - Tsabitah Rahmahdiyyah; Wahyu Eko Pujianto (Yayasan Adra Karima Hubbi, 2024)
Tlocor Marine Tourism is a one of a kind tour that is located in the city of Sidoarjo, which has become an icon of the city of Sidoarjo itself. This tour presents stunning natural scenery that is still beautiful. But not only that, but we can also enjoy culinary, fishing, and trips to the island in the Tlocor Marine Tourism area, namely Lusi Island. But unfortunately, the great potential of this tourism has not run effectively because many people still don’t know about this tourism. Due to this tour’s lack of promotion and branding, this tourist information is still word of mouth. Even though Sidoarjo is located in the middle lane of Surabaya - Malang where many tourism people to Malang can stop by Sidoarjo first, the integration of tourism and transportation routes is not implemented effectively which actually can increase the number of tourists. Therefore the researchers propose to integrate Tlocor Marine Tourism by using the implementation of the six pillars of a smart village such as smart people, smart mobility, smart governance, smart economy, smart living, and smart environment which will later have an impact on improving the economy of local communities. This research methodology uses descriptive qualitative methods with data that presents primary data and secondary data. From the descriptive method, the data that has been collected will be used as a description of the object under study which is described systematically. The results of this research will make Tlocor Marine Tourism better known and also make the village where Tlocor Marine Tourism is located become an independent village that supports many things, especially the economy of the local community. Researchers conducted several trainings and counseling for tourism parties which not only promote tourism but also create Smart Villages, create waste banks, digital training, halal certification, create literacy corners and so on. These things are expected to be sustainable because if they can continue to be sustainable, it will have a good impact on the surrounding community, namely increasing the local economy. There can even be job creation if this can be maintained properly.